AQUAPONICS: A serious game to promote aquaponics systems for local community development (2025)
The contributions of food production in aquaponic systems to the Sustainable Development Goals favor sustainable development. However, migrating from a traditional farming system to an alternative one requires a technology appropriation process involving initial recognition of its functioning. However, conventional education has not effectively transmitted this knowledge, especially in contexts other than formal education. Therefore, in this study, a serious board game was developed as a pedagogical strategy to increase the awareness and understanding of aquaponic food production of the general public and enhance sustainability practices in developing communities. The game board was designed with elements that facilitate the gaming experience for people with color blindness. The study was conducted in Colombia, and it included 1,096 people from 23 municipalities. For the analysis, four game groups were considered: young people, adults, elders, and a mixed team of participants of all age groups. The variables observed were the duration and number of attempts to win the game. A categorical principal component analysis (CATPCA) was used to analyze the correlation between the variables of the set of observations. The results show that the participants could recognize elements and the basic functioning of an aquaponics system. Furthermore, the experience gained during the game promotes cooperation in problem-solving and the motivation to continue learning, contributing to spreading the technology in communities.